1985
DOI: 10.1017/s0033291700020870
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical hypotheses of premenstrual tension syndrome

Abstract: EDITORIALBiochemical hypotheses of premenstrual tension syndrome 1 As information has evolved concerning the incidence of cyclical emotional changes preceding the onset of menses, the premenstrual tension syndrome (PMT) has gained increased attention in both the lay and professional literature. Although there has been some disagreement as to the exact nature, the time of occurrence, or even the existence of PMT (Koeske, 1981), there is considerable consensus that the PMT syndrome indeed exists (Janowsky et … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…The change in gender difference with age is not consistent with the biological or evolutionary theories. A biological account of gender difference, which suggests that the influence of female hormones as the cause ( Janowsky and Rausch, 1985 ), is not consistent with the similar gender difference in the level of depressive symptoms in the middle-age and the older adult groups. We would expect female hormone levels to be different in these two periods of the human lifespan.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The change in gender difference with age is not consistent with the biological or evolutionary theories. A biological account of gender difference, which suggests that the influence of female hormones as the cause ( Janowsky and Rausch, 1985 ), is not consistent with the similar gender difference in the level of depressive symptoms in the middle-age and the older adult groups. We would expect female hormone levels to be different in these two periods of the human lifespan.…”
Section: Discussionmentioning
confidence: 94%
“…Second, the biological susceptibility theory is based on the observation that clinical depression tends to be associated with events in the female reproductive cycle. Thus, the effect of female hormones has been proposed as a potential cause for the observed gender difference in depression ( Janowsky and Rausch, 1985 ). Third, evolutionary psychologists have noted that males tend to value physical appearance more than females when choosing a partner.…”
Section: Introductionmentioning
confidence: 99%
“…However, the pattern of change has proved inconsistent, with reports of greater autonomic reactivity in the follicular than in the luteal phases (3), the reverse effect (4), or only slight differences between the phases (5)(6)(7). Studies related to PMS have usually involved experimental testing during the premenstrual period rather than earlier portions of the luteal phase, since it has been suggested that central nervous system disturbances may lead to alterations of autonomic control and reactivity to stress (8,9). Yet investigations specifically focusing on this phase have also failed to identify robust patterns of response (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies bearing on the bodily sensations hypothesis have revealed mixed results. Although several literature reviews have concluded that fluctuating levels of ovarian hormones are not associated with the experience of premenstrual symptoms (Abplanalp, 1983;Clare, 1985;Gannon, 1985;Green, 1982;Janowsky, 1985;Rubinow & Roy-Byrne, 1984), a few studies have found a temporal association between hormonal changes and symptom experience Hammarback, Damber, & Backstrom, 1989;Schechter, Bachmann, Vaitukaitis, Phillips, & Saperstein, 1989). In addition, although some research findings suggest that women with prospectively confirmed reports of menstrually related mood disorder do not differ from asymptomatic control women in the amount or pattern of hormone secretion throughout the menstrual cycle (Rubinow et al, 1988;Sondheimer, Freeman, Scharlop, & Rickels, 1985), other research has found differences in estrogen and pregnanediol levels between PMS patients and controls (Dennerstein, Spencer-Gardner, Brown, Smith, & Burrows, 1984).…”
mentioning
confidence: 99%